THE EFFECT OF THE UTILIZATION OF OLIVE OIL AND COCONUT OIL COATING ON THE QUALITY AND SAVING OF RACES OF CHICKEN EGGS - M. Y. A., Anas; Wirapartha, M.; Okarini, I. A. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the effect of the use of olive oil coating and coconut oil coating treatment as a basis for maintaining the quality and shelf life of eggs. This research was conducted at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University, located on Jalan P.B Sudirman, Denpasar. The research was conducted for 40 days. The design used was a completely randomized design (CRD) factorial pattern consisting of 2 factors, namely; The first factor is eggs with coating, namely eggs treated without coating (TC), eggs treated with olive oil coating (DCz), and eggs treated with coconut oil coating (DCk). The second factor is the storage time at room temperature (27 ?), namely the storage of days 0, 10, 20, 30, and 40.With 3 treatments and 4 replications, and each repetition using 3 eggs of lohmann brown chicken so that the number of eggs used as many as 180 eggs. The variables observed were egg weight, egg yolk color, yolk index, haugh units, and egg pH. The data obtained were analyzed using ANOVA and Duncan's test. The results showed that the treatment of olive oil coating and coconut oil coating during the shelf life of 30 and 40 days on egg weight, egg yolk color, egg yolk index, and haugh unit had significantly different results (P <0.05) higher than without treatment. coating, while the pH of eggs from olive oil coating and coconut oil coating treatment was lower than that without coating but gave significantly different results (P <0.05). The results of this study can be concluded that the use of coatings of olive oil and coconut oil can increase the quality and shelf-life of eggs for up to 30 and 40 days.   Keywords : coating, olive oil, coconut oil, egg quality, shelf life.